Ten questions in sports engineering: generic athlete models for sports fluid dynamics - Giljarhus, K. E. T.; Terra, W. (Sports Engineering, 2026)
Computational and experimental investigations of flow over athletes are key elements of sports fluid dynamics to analyse performance and equipment design. However, the use of athlete-specific models often limits reproducibility, collaboration, and data sharing due to ethical and competitive constraints. This paper introduces and defines Generic Athlete Models as openly available, standardized geometries accompanied by benchmark flow datasets. The case is made that such models are essential to improve the reliability, comparability, and transparency of fluid dynamics research in sports. While only a few generic athlete models currently exist, this paper outlines clear directions for their further development and broader adoption.